Monitoring the Breeding Territory of the Short-Toed Eagle - Altai Zh. Zhatkanbaev; Nurlan M. Dosov; Aleksey A. Grachev; Ermek S. Musyrpanov; Sergey S. Shmygalev (Пернатые хищники и их охрана)
In the nesting seasons of 2013–2023, monitoring of the permanent nesting site of a pair of Short-Toed Eagles (Circaetus gallicus) was conducted in the southern shore of Lake Balkhash, in the transition landscape of wetland to desert biome, in a wooded area dominated by Turanga Poplar (Populus diversifolia). It was found that, at least during the 2017, 2021, and 2022 nesting seasons, nearly fully feathered chicks were eaten by an Asiatic Wildcat (Felis lybica ornata) shortly before they fledged from their nests. All nests observed during the monitoring periods were located in the uppermost center of a poplar tree crown. Starting in 2021, a DJI Mavic 2 PRO quadrocopter was used for monitoring.